2013
DOI: 10.1063/1.4804374
|View full text |Cite
|
Sign up to set email alerts
|

Emulating the paired-pulse facilitation of a biological synapse with a NiOx-based memristor

Abstract: We study the paired-pulse-induced response of a NiO x -based memristor. The behavior of the memristor is surprisingly similar to the paired-pulse facilitation of a biological synapse. When the memristor is stimulated with a pair of electrical pulses, the current of the memristor induced by the second pulse is larger than that by the first pulse. In addition, the magnitude of the facilitation decreases with the pulse interval, while it increases with the pulse magnitude or pulse width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 22 publications
3
97
1
1
Order By: Relevance
“…PPF is thus a form of short-term synaptic plasticity, and may be involved in several neuronal tasks, including simple learning, information processing, and sound-source localization. Recently, PPF was emulated in a NiOx-based memristor [14]. When the memristor is stimulated with a pair of electrical pulses, the current of the memristor induced by the second pulse is larger than that by the first pulse.…”
Section: Methodsmentioning
confidence: 99%
“…PPF is thus a form of short-term synaptic plasticity, and may be involved in several neuronal tasks, including simple learning, information processing, and sound-source localization. Recently, PPF was emulated in a NiOx-based memristor [14]. When the memristor is stimulated with a pair of electrical pulses, the current of the memristor induced by the second pulse is larger than that by the first pulse.…”
Section: Methodsmentioning
confidence: 99%
“…However, they are considered as very important elements in new types of computational systems. In particular, several works on memristive devices were done for the mimicking of synapse properties [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The activity in this directions are in progress and several important results have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…This instantaneous increase in current level, i.e., the conductance of the device is analogous to the memorization process of the human brain during the short term memory events through a stimulation/impression. [13] The conductivity of the device, i.e., the current start decaying gradually after each instantaneous increase in current level, i.e., in between two consecutive pulses. This decaying process is analogous to the memory loss in human memory immediately after input stimulation.…”
Section: Resistive Switching Memory Characterizationmentioning
confidence: 99%
“…[10] It is reported that memristor devices based on different material systems adequately mimic different important neuromorphic properties, such as potentiation, depression, learning, forgetting, etc. [11][12][13][14] Many novel materials including chalcogenides (Ge 2 Sb 2 Te 5 ), Ag/Si mixture, AlO x /HfO x bi-layer, etc. are reported as memristive material to mimic the synaptic functions.…”
mentioning
confidence: 99%